Continuous value shaping: A boundary concept for innovating service innovation approaches - Tilo Böhmann; Angela Roth; Gerhard Satzger; Carina Benz; Daniel Beverungen; Andreas Boes; Christoph Breidbach; Martin Gersch; Gerhard Gudergan; Jens Hogreve; Christian Kurtz; Barbara Langes; et al. (Electronic Markets, 2025)
Technological advancements and evolving value orientations reshape future value creation and pose new requirements for service innovation. While a variety of disciplines are developing new approaches to drive service innovation, this is primarily done in isolation and generates only fragmented solutions. Sociological theory has proposed “boundary objects” as an effective umbrella for communication and cooperation among communities. Therefore, we introduce continuous value shaping (CVS) as a boundary object describing service innovation approaches along five principles. We reflect on this concept through the different disciplinary lenses of researchers in service marketing, information systems, service engineering, sociology of work, and innovation management. These perspectives highlight how the CVS principles already connect to discourses within the individual disciplines. However, the CVS concept will not only provide an umbrella to embrace existing activities in different academic disciplines. It also assists to identify research themes that will benefit from uniting the power of these disciplines, and it can serve as an integrating framework to conceptualize complex service innovation approaches. Thus, the CVS concept should guide both researchers and practitioners to develop and implement novel innovation and transformation efforts—in and across organizations.
Keywords: M10; O30; 620; Continuous value shaping (CVS); Service research; Service innovation; Digitalization; Sustainability; Interdisciplinary research